PARTICIPATORY GOVERNANCE AND ITS EFFECTS ON MGNREGA SCHEME - RAJKHOWA, CHANDANA (International Journal of Psychosocial Rehabilitation, 2020)
Mahatma Gandhi National Rural Employment Guarantee Act, 2005 (MGNREGA) is a rural poverty reducing scheme through hundred days of guaranteed employment per year. This scheme has provided rights based social protection to both rural men as well as women. MGNREGA is a policy solution to rural poverty in India. It has offers a unique rights based employment guarantee to reduce income and food security in rural areas. The experiences of participation in MGNREGA varied state to state depending on how MGNREGA wages compared to market wages, awareness and implementation of the programme. The marginalized section of the society is helped out by MGNREGA scheme. It has inaugurated a remarkable process in the empowerment of poor. The government is trying to address MGNREGA specifically as a tool of empowerment for the most vulnerable sections of the village communities because they are victims of social exclusion and political marginalization. People’s participation from the marginalized section of the society in governing process has enhanced the democracy in India. The participation of people has effects on MGNREGA scheme by enhancing the meaning of democracy in a developing country like India. This paper will try to focus on the process of people’s participation in a democratic country through economic decentralization and how people’s participation in MGNREGA has contributed to the enhancement of the values of democracy in India.